2019
DOI: 10.3390/ijms20081886
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Analysis of Two Contrasting Maize Inbred Lines Provides Insights into the Mechanism of Salt-Stress Tolerance

Abstract: Salinity is a major abiotic stress that limits maize yield and quality throughout the world. We investigated phosphoproteomics differences between a salt-tolerant inbred line (Zheng58) and a salt-sensitive inbred line (Chang7-2) in response to short-term salt stress using label-free quantitation. A total of 9448 unique phosphorylation sites from 4116 phosphoproteins in roots and shoots of Zheng58 and Chang7-2 were identified. A total of 209 and 243 differentially regulated phosphoproteins (DRPPs) in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 89 publications
2
25
0
Order By: Relevance
“…We also observed increased proline content and POD activity in response to PEG treatment in mutant vp16 (Figure 5A), which resulted in more antioxidant activity and ROS removal, consistent with our previous findings [47]. Increased accumulation of peroxidase, an integral component of the glutathione-ascorbate cycle, is critical for H 2 O 2 scavenging and improving tolerance to oxidative stress [78]. The abundance of POD was previously reported in salt-tolerant [77] and drought-tolerant maize lines [63,80] suggesting that enhanced synthesis of glutathione and antioxidants, together with other stress-protective and -responsive proteins, is a common strategy for drought-tolerant plants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also observed increased proline content and POD activity in response to PEG treatment in mutant vp16 (Figure 5A), which resulted in more antioxidant activity and ROS removal, consistent with our previous findings [47]. Increased accumulation of peroxidase, an integral component of the glutathione-ascorbate cycle, is critical for H 2 O 2 scavenging and improving tolerance to oxidative stress [78]. The abundance of POD was previously reported in salt-tolerant [77] and drought-tolerant maize lines [63,80] suggesting that enhanced synthesis of glutathione and antioxidants, together with other stress-protective and -responsive proteins, is a common strategy for drought-tolerant plants.…”
Section: Discussionsupporting
confidence: 91%
“…Pentose phosphate pathway has been significantly enriched in response to various abiotic stresses [51,77]. Additionally, the NADPH resulting from the pentose phosphate pathway is the cofactor essential for the conversion of oxidized glutathione to reduced glutathione [78]. Glutathione is critical for redox homeostasis maintenance as one of the major antioxidants involved in ROS elimination [51,79].…”
Section: Discussionmentioning
confidence: 99%
“…Plant propagation and development are two important aspects that could largely determine the life cycle and economic values of different crops. The special issue studied different plants species, including an energy plant Jatropha curcas [18], a biofuel tree Pongamia [19], and three economic crops [20,21,22]. Liu et al used combined analyses of the phosphoproteomics, physiological characteristics, and ultrastructure studies to identify the responses of J. curcas seedlings under chilling, and revealed significantly changed phosphoproteins under chilling stress [18].…”
mentioning
confidence: 99%
“…A comparative study between the salt resistance and sensitive cultivars with very close genetic background will undoubtedly help to explore the key regulator. On the basis of this idea, Zhao et al conducted a phosphorproteomic analysis between two maize inbred lines showing different resistance to salt stress, and found that the enhancement of potassium and sodium transportation, carbon, and redox-related metabolism could increase the salt resistance in maize [19]. In this issue, Yu et al applied a newly developed Phos-tagTM technology to identify 21 phosphorylated peptides of AGPase [20].…”
mentioning
confidence: 99%
“…In eukaryotes, the most common class of phosphorylation is found on serine (S), threonine (T), and tyrosine (Y) residues [ 96 , 97 ] in which the γ-phosphate group covalently reacts with the hydroxyl group of amino acid side chains by potein kinases [ 98 ]. A large scale of phosphosites and phosphoproteins has been identified using phosphoproteomic technologies in many cereals such as rice [ 27 , 28 , 31 , 99 , 100 , 101 , 102 , 103 ], wheat [ 104 , 105 , 106 , 107 , 108 ], barley [ 109 , 110 ], and maize [ 111 , 112 , 113 , 114 , 115 ]. Phosphoserine (>90%) is a major phosphorylation type of rice endosperm, followed by phosphothreonine (6–9%) and phosphotyrosine (0.1–0.4%) [ 28 , 31 ].…”
Section: Starch Biosynthesis-related Proteins Targeted By Ptmsmentioning
confidence: 99%